Changes in free amino acid and protein polymerization in wheat caryopsis and endosperm during filling after shading - Ma, Hongliang; Yang, Yongheng; Wu, Dongming; Xiang, Gang; Luo, Ting; Huang, Xiulan; Yang, Hongkun; Zheng, Ting; Fan, Gaoqiong (Frontiers in Plant Science, 2024)
Over the past several decades, a decreasing trend in solar radiation has been observed during the wheat growing season. The effects of shade stress on grain yield formation have been extensively studied. However, little information on shade stress's effects on protein formation warrants further investigation. Two wheat cultivars were grown under three treatments, no shade as the control group (CK), shading from the joint to the anthesis stage (S1), and shading from the joint to the mature stage (S2), to investigate the effects of shade stress on the free amino acids of the caryopsis and endosperm and protein accumulation during grain filling. The dry mass of caryopsis and endosperm was significantly decreased under shade stress, whereas Glu, Ser, Ala, and Asp and protein relative content increased during grain filling. The observed increases in total protein in S1 and S2 were attributed to the increases in the SDS-isoluble and SDS-soluble protein extracts, respectively. S1 improved polymer protein formation, but S2 delayed the conversion of albumins and globulins into monomeric and polymeric proteins. Moreover, shade stress increased the proportion of SDS-unextractable polymeric protein, which represented an increase in the degree of protein polymerization. The polymerization of protein interrelations between protein components and accumulation in caryopsis and endosperm provided novel insights into wheat quality formation under shade stress.